1990
DOI: 10.1161/01.cir.82.4.1169
|View full text |Cite
|
Sign up to set email alerts
|

Early evidence of endothelial vasodilator dysfunction at coronary branch points.

Abstract: Intracoronary acetylcholine produces endothelium-dependent dilation of normal coronary arteries and paradoxical constriction of atherosclerotic vessels. Regional differences in endothelium-dependent vasomotion, however, have not been studied in relation to the nonuniform development of atherosclerosis. We compared the vasomotor response to increasing doses of acetylcholine of angiographically smooth coronary artery segments prone to atherosclerosis (coronary branch points) with segments remote from branch poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
5

Year Published

1995
1995
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 25 publications
(6 reference statements)
3
56
1
5
Order By: Relevance
“…When acetylcholine was infused intravenously, normal controls showed a vasodilatory response, but responses were reduced or vasoconstrictive in patients with hypertension, 13 diabetes, 15 hypercholesterolemia, 14 congestive heart failure 28 or atherosclerosis. 5,21,[23][24][25] Similarly, increases in flow subject the endothelium to increased shear stress, which stimulates the NO-cGMP pathway, so that FMD is also dependent on endothelial cells. Abnormal FMD has been shown in patients with cardiac risk factors and in atherosclerosis.…”
Section: No-dependent Penile Erectionmentioning
confidence: 99%
See 2 more Smart Citations
“…When acetylcholine was infused intravenously, normal controls showed a vasodilatory response, but responses were reduced or vasoconstrictive in patients with hypertension, 13 diabetes, 15 hypercholesterolemia, 14 congestive heart failure 28 or atherosclerosis. 5,21,[23][24][25] Similarly, increases in flow subject the endothelium to increased shear stress, which stimulates the NO-cGMP pathway, so that FMD is also dependent on endothelial cells. Abnormal FMD has been shown in patients with cardiac risk factors and in atherosclerosis.…”
Section: No-dependent Penile Erectionmentioning
confidence: 99%
“…3,5,[16][17][18][19][20]22,29 Importantly, many of these studies also showed that vasodilation to nitrates, which act directly on smooth muscle in an endothelial-independent manner, was preserved. [13][14][15][16]18,21,23,24 Moreover, N G -monomethyl L-arginine (L-NMMA), a NO synthase inhibitor, blunted the vasodilatory response to acetylcholine and FMD, but did not affect nitroprusside-induced vasodilation. 30,31 Endothelial dysfunction contributes to atherosclerosis The NO-cGMP pathway becomes impaired before the development of atherosclerosis and its impairment likely contributes to the pathogenesis of atherosclerosis.…”
Section: No-dependent Penile Erectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like atherosclerosis, endothelial dysfunction is evidenced earlier in the bifurcations of human coronary arteries 19 . In the presence of coronary atherosclerosis, the intensity of endothelial dysfunction is directly related to the atherosclerotic damage 5 .…”
Section: Clinical Implications -The Implications Of Endothelial Dysfumentioning
confidence: 99%
“…In contrast, endothelial dysfunction appears to play a pathogenic role in the initial development of atherosclerosis [7][8][9] and of unstable coronary syndromes 10 , being associated with atherosclerotic disease risk factors [11][12][13][14][15][16][17][18] , and being present even before vascular involvement becomes evident 6,[19][20][21] .…”
mentioning
confidence: 99%